The Forgotten Early Chinese-Language Newspaper in Latin America: History and Role of Hoy Men Kong Po in Cuba - Zigang, Wang; Fangjun, Liang; Qixin, Xue (Sinología hispánica. China Studies Review, 2025)
Early Chinese-language newspapers in Latin America were a vital carrier of social memory for the Chinese community and a key window for academics to understand the social situation of the Chinese diaspora in the mentioned region. As the longest-running Chinese-language newspaper in Cuba, the centre of Chinese-language media in Latin America in the last century, Hoy Men Kong Po (開明公報) was highly representative and significant. In this study, we conducted an in-depth excavation of this newspaper stored in the National Library of China. We sorted out and reviewed the historical context and different stages of its establishment. Subsequently, based on a structural weekly sampling study of more than a thousand copies of this newspaper from 1955 to 1959, we identified six major classifications of its contents and analysed their corresponding characteristics and impacts on the Chinese community in Cuba.